2010
DOI: 10.3109/09537100903487599
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume on admission correlates with impaired response to thrombolysis in patients with ST-elevation myocardial infarction

Abstract: Mean platelets volume (MPV) has been shown to correlate with impaired reperfusion and increased mortality in patients with ST-elevation myocardial infarction (STEMI) treated with primary precutaneous coronary intervention (PCI). We aimed to study whether the same association exists in STEMI patients treated with thrombolysis. Included in the study were STEMI patients receiving thrombolysis. Thrombolysis failure was defined as a need for rescue precutaneous coronary intervention (PCI), in-hospital mortality, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 15 publications
3
40
0
1
Order By: Relevance
“…In one of them, MPV was found to be elevated in patients with STEMI (20). In another, Pereg et al (21) found an association between unsuccessful thrombolytic therapy and an increased MPV in patients with STEMI. Also, Chu et al (22) reported an association between MPV and acute myocardial infarction in a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 94%
“…In one of them, MPV was found to be elevated in patients with STEMI (20). In another, Pereg et al (21) found an association between unsuccessful thrombolytic therapy and an increased MPV in patients with STEMI. Also, Chu et al (22) reported an association between MPV and acute myocardial infarction in a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 94%
“…In the study by Pereg et al (25) it was reported that thrombolysis failure defined as lack of ST-segment resolution at 90 minutes and need for rescue PCI, in-hospital mortality, unplanned PCI during hospitalization or complete occlusion of the culprit artery in a follow up angiography was significantly higher in patients with elevated MPV. But specific data about the relationship between MPV and ST -segment resolution has not been mentioned in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Başka bir çalışmada, perkutan girişim ile tedavi edilen STEMI'lı hastalarda MPV'nin, kötü anjiografik reperfüzyon ve mortalitenin bağımsız bir göstergesi olduğu gösterilmiştir (34). STEMI'lı hastalarda yapılan başka bir çalışmada, başarısız trombolitik tedavi ve MPV arasında ilişki bulunmuştur (35). PCI yapılan STEMI'lı hastalarda, infarkt ilişkili arterin açıklığının tahmininde MPV'nin faydalı olabileceği bildirilmiştir (36).…”
Section: Gereç Ve Yöntemlerunclassified